LIMITED LIABILITY DALAM LIMITED LIABILITY PADA KONSTRUKSI PERUSAHAAN KELOMPOK PIRAMIDA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Applicability of limited liability in corporate groups with pyramid construction creates a legal loophole in the form of a limited liability within a limited liability. To prevent moral hazard, it is necessary to stipulate new law that limits the number of levels in a corporate group.